The Feasibility Study of Financial Aspects and Demand of Community to the Construction of the Cempaka Lima General Hospital in Banda Aceh - Brury Apriadi Husaini; Munifah Abdat; Martunis Martunis (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Based on the analysis of financial aspects, PP was shorter than the life of the investment (10 years), namely 8 years,1 month and 5 days;Positive NPV of Rp.387,970,363,668, -; PI is 5; IRR is 10.18%; and ARR which is 138%. demand of community found 84% of respondents chose private and government hospitals, 90% of respondents conducted examinations at general practitioners, 97% of respondents chose health services because of complete facilities, 98% of respondents did blood pressure checks, 97% of respondents received prescriptions, 90 % of respondents access outpatient services, 59% of respondents use insurance, and the average distance of respondents from their place of residence to health services is less than 2 km (90%). Hospitals need to increase revenue by adding service products and optimize non-medical revenue to support income and immediately establish operational cooperation with BPJS considering that most of the people who access health services use JKN.